Utilization of Neutral Zone Technique for Rehabilitation of Atrophic Maxillary and Mandibular Ridges: A Clinical Report - Kukreja, Harpreet Singh; Narula, Siddharth; Sharma, Vivek; Khandelwal, Meenakshi; Lath, Vivek; Chhonkar, Devendra Pal Singh (Journal of Orofacial Research, 2019)
The neutral zone technique is an alternative approach for the construction of the complete dentures. It is most effective for dentures where there is a highly atrophic ridge. The technique aims to construct a denture that is shaped by muscle function and is in harmony with the surrounding oral structures. This clinical report describes the fabrication of complete dentures for a patient with poorly formed both maxillary and mandibular ridges.